2019
DOI: 10.1002/admt.201900600
|View full text |Cite
|
Sign up to set email alerts
|

Remotely and Sequentially Controlled Actuation of Electroactivated Carbon Nanotube/Shape Memory Polymer Composites

Abstract: A shape memory material, when deformed to a temporary shape, can recover to its original shape under an external stimulus. [1] Owing to its low cost, ease in manufacturing, and high shape recovery ratio, shape memory polymer (SMP) has attracted more attention than metal and ceramic based shape memory materials. [1a,2] For SMPs, most of the research effort so far has focused on thermally activated shape recovery process using direct heating with an external heater. [3] In order to eliminate the external heate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 45 publications
0
41
0
Order By: Relevance
“…The conductive carbon filaments allowed for electrical actuation by resistive heating, leading to recovery above 95% in approx. 75 s. 58 Carbon nanotubes (CNTs) were introduced in PLA instead by Liu et al 61 They found a dependency of the volume resistivity on the raster angle as well as the temperature, especially above approx. 70 C. Resistive heating thus resulted in different time-dependencies of the temperatures reached in the samples.…”
Section: Pla Compositesmentioning
confidence: 99%
“…The conductive carbon filaments allowed for electrical actuation by resistive heating, leading to recovery above 95% in approx. 75 s. 58 Carbon nanotubes (CNTs) were introduced in PLA instead by Liu et al 61 They found a dependency of the volume resistivity on the raster angle as well as the temperature, especially above approx. 70 C. Resistive heating thus resulted in different time-dependencies of the temperatures reached in the samples.…”
Section: Pla Compositesmentioning
confidence: 99%
“…Besides, the human–machine interaction provides the approaches of obtaining human gesture and motion signals [ 100 ]. In addition, CNT devices guarantee the remotely controlled actuation [ 101 ], and wireless energy transfer [ 102 ]. The upcoming efforts should be put into the self-powered sensing system by energy harvesting from the environment and motion energy.…”
Section: Emerging Opportunities For Carbon Nanotube Applicationsmentioning
confidence: 99%
“…Most of the SMPs already processed by AM do not present electroactive properties and, therefore, it is common to incorporate responsive particles into polymeric blends, forming polymer-based electroactive composites. In this context, PLA, a thermosensitive polymer commonly used in AM due to its extrudability and shape memory properties, was blended with carbon nanotubes (CNT) to prepare electroactive composites [ 75 ]. The PLA-based composite was acquired in a filament shape and then processed by FFF.…”
Section: Non-conventional Technologies and Most Common Polymers To Produce Eapsmentioning
confidence: 99%